Subchronic Exposure to Fenthion Induces Hematological Changes in Liver Tissue of African Catfish Clarias gariepinus. Issue 4 (20th October 2016) - Nwani, Christopher Didigwu; Somdare, Peace Onas; Ukonze, Juliana Adimonye; Ejere, Vincent Chikwendu; Nwadinigwe, Alfreda O.; Nwani, Jacinta Chinedu; Odo, Gregory Ejike; Ugbor, Ogechi Nnabuchi
Abstract: In this study, African Catfish (also known as Sharptooth Catfish) Clarias gariepinus were exposed to sublethal concentrations of fenthion of 2.0, 4.0, and 8.0 mg/L for 21 d and allowed to recover for 7 d to investigate the potential for hematological changes. Whole blood was sampled on days 1, 7, 14, and 21 postexposure and after a 7‐d recovery period. During exposure, fenthion caused a reduction in red blood cell counts, hemoglobin concentration, and packed cell volume. There was an increase in white blood cell counts but no significant difference in mean corpuscular hemoglobin concentration, mean corpuscular volume, and mean corpuscular hemoglobin. Both increases and decreases were observed in white blood cell differentials. After the 7‐d recovery period, both increases and decreases were observed in the hematological parameters. These results reveal that sublethal concentrations of fenthion can cause hematological alterations in African Catfish and that the substance should be used with caution. Received October 20, 2015; accepted May 4, 2016 Published online October 20, 2016